Influence of Silica Exposure for Lung Silicosis Rat. (13th December 2021) - Jiao, Jie; Li, Li; Yao, Wu; Qin, Weidong; Hao, Changfu; Lu, Lingeng
Abstract : Objective . To investigate the influence of silica exposure on the expression of connective tissue growth factor (CTGF), transforming growth factor beta-1 (TGF- β 1), and platelet-derived growth factor (PDGF) in lung silicosis rat. Methods . Wistar rats were divided into an experimental group and a control group. In the experimental group, rats were exposed to silica by intratracheal instillation. In the control group, rats were exposed to physiological saline by intratracheal instillation. After 45 days, we compared the level of fibrosis and CTGF, TGF- β 1, and PDGF in the lungs by immunohistochemistry or reverse transcription-polymerase chain reaction between the two groups. Results . The results showed that the expression levels of CTGF, TGF- β 1, and PDGF mRNA were significantly higher in the experimental group than those in the control group (P < 0.05 ). The positive staining of CTGF, TGF- β 1, and PDGF mRNA was found in the cytoplasm, especially in the silicotic nodules of the hyalinisation section and cell endochylema of the alveolar macrophages, type II pneumonocytes, and lung tracheal epithelium. There were significantly positive correlations between CTGF, TGF- β 1, and PDGF expressions (P < 0.05 ). A protein–protein interaction analysis showed interactions between TGF- β 1, CTGF, and PDGF. Conclusions . TGF- β /CTGF signaling pathway plays an important role in silicosis. Silicon dioxide exposure can induce the expression of CTGF, TGF- β 1, and PDGF.